Trophic Structure and a Temporal Shift in Trophic Diversity of Mobile Consumers in a Subarctic Estuary - Jillian R. St. George; Stephen D. Petersen; James D. Roth; Steven H. Ferguson; David J. Yurkowski (Estuaries and Coasts, 2024)
Quantifying trophic relationships within and between species in terms of trophic position, ontogeny and trophic diversity provides information on community-level structure and function. Little attention has been focused on examining the trophic structure and temporal changes of communities in freshwater-marine coupled systems in the subarctic and associated impacts of anthropogenic activity on trophic interactions. Therefore, the objective of this study was to quantify the trophic position of mobile consumers (15 species in total) within the lower Churchill River area (Churchill, Manitoba, Canada), examine trophic position variation in relation to ontogeny, and measure the trophic diversity of a fish assemblage before (1993–1995) and after (2019–2020) the installation of the Churchill River weir in the late 1990s. We used stable isotopes (δ 13 C and δ 15 N) to quantify individual and group-level variation in trophic position of thirteen fish species and two seal species and also assessed six community-level metrics of a three fish species assemblage between time periods. Overall, species that mainly foraged on freshwater resources occupied lower trophic positions than species that mainly consumed marine resources. Trophic position increased with fish age only in cisco, fourhorn sculpin, Greenland cod and northern pike. A temporal shift from a trophically diverse to a more trophically redundant fish assemblage occurred between 1993–1995 and 2019–2020. As a result, these predator species now play similar trophic roles. Information on the long-term change in trophic structure of this sub-Arctic estuarine system may help with understanding how anthropogenic activity and climate change have influenced the trophic diversity of a fish assemblage inhabiting this system.